Sistem Kendali dan Monitoring Irigasi pada Rumah Kaca Berbasis Bluetooth dengan Metode Fuzzy Logic - Sak, Erwin; Yulianto, Andik; Sabariman, Sabariman (Telcomatics, 2024)
In general, plantations using greenhouses or Green Houses are faced with various obstacles. Changes in temperature and humidity in the room are unpredictable and you have to determine the right time to water and determine which plants to plant by seeing whether the plants can tolerate the temperature and humidity levels in the greenhouse room and estimating how much watering should be done.From these problems, the author created a Green House Prototype and an irrigation system using the Fuzzy Method which is capable of monitoring and watering plants automatically.Based on the results of the analysis by applying the Fuzzy method in the irrigation system, the author can control the watering of Strawberry plants and adjust the Temperature, Humidity and moisture levels to a good ecosystem for the growth of Strawberry plants in the Prototype Green House.